DC magnetron sputtered TiO2 thin film as efficient hole blocking layer for perovskite solar cell - Saheed, M.S.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
The ultra-thin film of metal oxide were fabricated via DC-magnetron sputtering to acts as the hole blocking layer. The traditional dye absorption material were replaced by the fourth generation light harvesting material, the CH3NH3PbI3 which deemed to reach the PV efficiency limit. The complete conversion of PbI2 into CH3NH3PbI3 crystal structure vital in lowering the internal series resistance. With this new light harvesting material were used able to achieve 7.75 efficiency via sequential two step deposition of perovskite. © 2017 IEEE.